Evaluation of Philippine-sourced clay particles as coating agents of cacao pods and carrier of entomopathogen against cacao pest, Helopeltis bakeri Poppius - Albacete, Sharin C.; Amalin, Divina M.; Carvajal, Thaddeus M.; Wise, John C. (Frontiers in Agronomy, 2023)
Choice and no-choice tests were performed to evaluate Philippine-sourced clay particles as coating agents of cacao pods to deter cacao mirid bug (CMB), Helopeltis bakeri Poppius feeding, in comparison with the commercially available particle film (US kaolin Surround®). To determine the most efficient local clay particles in protecting the pods from CMB feeding, , Philippine-sourced kaolin (PH kaolin), zeolite (PH zeolite), bentonite (PH bentonite), US kaolin, water, and a commercial synthetic insecticide thiamethoxam (Actara®) were tested. Among the Philippine clay particles tested, PH zeolite showed significant coating and deterred CMB from feeding. The US Kaolin and zeolite were also tested as carriers of entomopathogenic fungi, M. anisopliae. Results showed that zeolite is a good carrier of the spores of M. anisopliae as its effects to deter CMB feeding started 24 hours after exposure. This was confirmed by positive M. anisopliae extraction from dead CMB through potato dextrose agar (PDA) plating.